Development of Interactive Learning Media Assisted by Augmented Reality on Solar System Material to Enhance Elementary School Students’ Learning Interest - Wini Juanita; Deddy Sofyan; Lina Novita (AL-ISHLAH: Jurnal Pendidikan, 2026)
Learning processes in elementary schools that are still dominated by conventional media, such as textbooks and two-dimensional images, tend to cause student boredom and low learning interest. Therefore, the development of Augmented Reality (AR)–based learning media is needed to present learning materials in a more interactive and contextual manner in order to enhance students’ interest and learning experiences. This study aims to develop interactive learning media assisted by Augmented Reality on the Solar System topic for elementary school students and to examine the feasibility and effectiveness of the media in improving students’ learning interest and learning outcomes. This research employed the ADDIE development model, consisting of Analyze, Design, Develop, Implement, and Evaluate stages. The effectiveness of the media was measured by comparing pretest and posttest results using the gain index analysis.  The validation results show that the AR learning media Tata Surya is included in the very feasible category, with a score of 96% from media experts, 94% from material experts, and 96% from language experts. an increase in learning outcomes from 34.14 to 90.36, as well as an increase in learning interest from 42.68 to 86.79. The increase in learning outcomes is reinforced by an average N-gain value of 0.85 which is included in the high category. In addition, user responses are in the very good category, with teacher assessments of 93% and students of 90%. Based on these findings, it can be concluded that the interactive learning media assisted by Augmented Reality on the Solar System topic is highly feasible and effective in enhancing elementary school students’ learning interest and learning outcomes.